Penguatan Nilai-nilai Multikultural Melalui Pelatihan Pembuatan Media Animasi Bagi Siswa SMP Swasta Nommensen - Junita Yosephine Sinurat; Isrina Siregar; Merci Robbi Kurniawanti; Andre Mustofa Meihan; Yoan Mareta; Lisa Rukhmana; Destri Yaldi (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
This community service program was implemented as an effort to strengthen multicultural values, with the aim of addressing partner issues, including findings of intolerance, discriminatory behavior, a lack of empathy for others, and bullying stemming from students' lack of acceptance of differences. The implementation method for this community service activity was as follows: 1) conducting a social and cultural approach with partners to gain a deeper understanding of the problems faced by participants, 2) designing and implementing training on creating animated videos based on multicultural values, 3) mentoring participants in creating animated videos based on multicultural values, and 4) conducting program reflection and evaluation. The results of this activity were that 25 out of 30 participants successfully created animated videos. However, all participants understood that diversity is not a threat but a source of beauty and harmony, enabling them to understand and maintain the integrity of the nation and state by mutually respecting differences in ethnicity, religion, and race.